Extended-Spectrum β-Lactamase-Producing Enterobacterales - Kondo, Sumalee (Asian Medical Journal and Alternative Medicine, 2022)
Extended-spectrum β-lactamases-producing Enterobacterales is one of the global health concern due to rapid global spread and threatening infections. It is known as “superbugs” causing both hospital-acquired and community-acquired infections. ESBLgenes dissemination is associated with mobile genetic elements on plasmid resulting in rapid transmission. Emerging of ESBL producers can occur by horizontal gene transfer. It is suggested that screening for ESBL colonization should be carried out in the high-risk groups. Moreover, appropriate antibiotic use for treatment is imperative to prevent development of bacterial resistance against new antibiotics. Global surveillance of extended-spectrum β-lactamase producing Escherichia coli is currently carried out with a tricycle protocol. It is crucial to encourage active surveillance and infection control to prevent ESBL genes transmission.